Analysis of The Impact of Fuel Oil Price Increases on Fishermen's Income in Kendari City - Wa Ode Eka Saputri Kaaji; Muhammad Aswar Limi; Munirwan Zani (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
The fisheries sector is essential to Indonesia's economy and food security but is faced with significant challenges, such as fluctuations in fuel oil (BBM) prices. This study analyzes the differences in fishermen's income in Petoaha Village, Nambo Sub District, Kendari City, before and after the fuel price increase in November 2022. This study uses a quantitative design with a descriptive approach to assess the economic impact of the fuel price increase on fishermen's income. The research was conducted from December 2022 to June 2023 and involved 55 respondents selected through a simple random sampling method. The variables studied include operational costs, revenue, and fishermen's income, with the application of a paired sample t-test as the primary analysis tool. The results showed significant changes in fishermen's cost structure and income after the fuel price increase. The average income of fishermen decreased by IDR 1,627,778 per month after the fuel price increase. Further details of the cost, revenue, and income analysis outlined in this study illustrate how fluctuating fuel costs change the economic dynamics of fishers, which is essential for policymakers and stakeholders in fisheries to understand and address.